Novel Candidate Genes and Regions for Childhood Apraxia of Speech (CAS) Identified by Array Comparative Genomic Hybridization - Laffin, Jennifer J.S. (2012)
PURPOSE: The goal of this study was to identify new candidate genes and genomic copy number variations associated with a rare, severe, and persistent speech disorder termed Childhood Apraxia of Speech (CAS). CAS is the speech disorder segregating with a mutation in FOXP2 in a multigenerational London pedigree widely studied for its role in the development of speech-language in humans. METHODS: Twenty-four participants suspected to have CAS were assessed using a comprehensive protocol that samples speech in challenging contexts. All participants met clinical-research criteria for CAS. Array comparative genomic hybridization analyses were completed using a customized 385K Nimblegen array (Roche Nimblegen, Inc.) with increased coverage of genes and regions previously associated with CAS. RESULTS: A total of 16 copy number variations (CNVs) with potential consequences for speech-language development were detected in 12 or half of the 24 participants. The CNVs occurred on 10 chromosomes, 3 of which had 2–4 candidate regions. Several participants were identified with CNVs in 2–3 regions. Additionally, one participant had a heterozygous FOXP2 mutation and a CNV on chromosome 2, and one participant had a 16p microdeletion and CNVs on chromosomes 13 and 14. CONCLUSIONS: Findings support the likelihood of heterogeneous genomic pathways associated with CAS.